No tag edit access

C. Replacement

time limit per test

2 secondsmemory limit per test

256 megabytesinput

standard inputoutput

standard outputDaniel has a string *s*, consisting of lowercase English letters and period signs (characters '.'). Let's define the operation of replacement as the following sequence of steps: find a substring ".." (two consecutive periods) in string *s*, of all occurrences of the substring let's choose the first one, and replace this substring with string ".". In other words, during the replacement operation, the first two consecutive periods are replaced by one. If string *s* contains no two consecutive periods, then nothing happens.

Let's define *f*(*s*) as the minimum number of operations of replacement to perform, so that the string does not have any two consecutive periods left.

You need to process *m* queries, the *i*-th results in that the character at position *x*_{i} (1 ≤ *x*_{i} ≤ *n*) of string *s* is assigned value *c*_{i}. After each operation you have to calculate and output the value of *f*(*s*).

Help Daniel to process all queries.

Input

The first line contains two integers *n* and *m* (1 ≤ *n*, *m* ≤ 300 000) the length of the string and the number of queries.

The second line contains string *s*, consisting of *n* lowercase English letters and period signs.

The following *m* lines contain the descriptions of queries. The *i*-th line contains integer *x*_{i} and *c*_{i} (1 ≤ *x*_{i} ≤ *n*, *c*_{i} — a lowercas English letter or a period sign), describing the query of assigning symbol *c*_{i} to position *x*_{i}.

Output

Print *m* numbers, one per line, the *i*-th of these numbers must be equal to the value of *f*(*s*) after performing the *i*-th assignment.

Examples

Input

10 3

.b..bz....

1 h

3 c

9 f

Output

4

3

1

Input

4 4

.cc.

2 .

3 .

2 a

1 a

Output

1

3

1

1

Note

Note to the first sample test (replaced periods are enclosed in square brackets).

The original string is ".b..bz....".

- after the first query
*f*(hb..bz....) = 4 ("hb[..]bz...." → "hb.bz[..].." → "hb.bz[..]." → "hb.bz[..]" → "hb.bz.") - after the second query
*f*(hbс.bz....) = 3 ("hbс.bz[..].." → "hbс.bz[..]." → "hbс.bz[..]" → "hbс.bz.") - after the third query
*f*(hbс.bz..f.) = 1 ("hbс.bz[..]f." → "hbс.bz.f.")

Note to the second sample test.

The original string is ".cc.".

- after the first query:
*f*(..c.) = 1 ("[..]c." → ".c.") - after the second query:
*f*(....) = 3 ("[..].." → "[..]." → "[..]" → ".") - after the third query:
*f*(.a..) = 1 (".a[..]" → ".a.") - after the fourth query:
*f*(aa..) = 1 ("aa[..]" → "aa.")

Codeforces (c) Copyright 2010-2017 Mike Mirzayanov

The only programming contests Web 2.0 platform

Server time: Dec/13/2017 19:52:08 (c5).

Desktop version, switch to mobile version.

User lists

Name |
---|